2021
DOI: 10.1016/j.isci.2020.101897
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying evolving toxicity in the TAML/peroxide mineralization of propranolol

Abstract: Summary Oxidative water purification of micropollutants (MPs) can proceed via toxic intermediates calling for procedures for connecting degrading chemical mixtures to evolving toxicity. Herein, we introduce a method for projecting evolving toxicity onto composite changing pollutant and intermediate concentrations illustrated through the TAML/H 2 O 2 mineralization of the common drug and MP, propranolol. The approach consists of identifying the key interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…This means fully converting the contaminants to a gaseous form, water, salts, and minerals [ 145 ]. However, several photodegradation reactions may lead to toxic intermediate compounds, which can harm the environment [ 146 ]. The total organic carbon (TOC) quantification method can be employed to evaluate the mineralization of a contaminant achieved by photocatalysis.…”
Section: Photocatalytic Applicationsmentioning
confidence: 99%
“…This means fully converting the contaminants to a gaseous form, water, salts, and minerals [ 145 ]. However, several photodegradation reactions may lead to toxic intermediate compounds, which can harm the environment [ 146 ]. The total organic carbon (TOC) quantification method can be employed to evaluate the mineralization of a contaminant achieved by photocatalysis.…”
Section: Photocatalytic Applicationsmentioning
confidence: 99%
“…The simplest stoichiometric mechanism of Fe-TAML-catalyzed oxidations by H 2 O 2 in aqueous media is straightforward. , The iron(III) resting state of any Fe-TAML catalyst is activated by an oxidant such as H 2 O 2 (step 1), and the active catalyst formed then attacks an electron donor, S (step 2). If S is a dye, the primary products are usually oxidized fast (step 3), which is typically not the case for more difficult-to-oxidize targets. , [ L Fe III ] 0.25em ( resting state ) + normalH 2 normalO 2 active 0.25em catalyst 0.25em ( k I ) active 0.25em catalyst + normalS [ L Fe III ] + primary 0.25em product 0.25em ( k II ) active 0.25em catalyst + primary 0.25em product [ L Fe III ] + product / normals 0.25em ( fast ) …”
Section: Introductionmentioning
confidence: 99%
“…If S is a dye, the primary products are usually oxidized fast (step 3), which is typically not the case for more difficult-to-oxidize targets. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] The application of iron-TAMLs [12] (which are small molecule mimics of natural cytochrome P450 enzymes) as catalysts for the oxidative destruction of micropollutants in water by hydrogen peroxide, presents a promising alternative because studies have shown that iron-TAML/hydrogen peroxide oxidation systems can degrade a range of organic micropollutants. [13][14][15][16][17][18][19][20][21] The catalytic performance of iron catalysts with the TAML structural motif (e. g., TAML B, Scheme 1) has been improved through an iterative design protocol over many years with the latest design incorporating two amidate and two sulfonamidate donors within the macrocyclic ring (TAML C, Scheme 1). [22][23][24][25][26][27] During this improvement process, electron-withdrawing groups on the ligand framework were found to both increase the oxidising power of the activated iron-TAMLs and also cause the pH at which the maximum oxidation rate occurs to move closer to neutral.…”
Section: Introductionmentioning
confidence: 99%